2000
DOI: 10.1016/s1097-2765(00)00139-8
|View full text |Cite
|
Sign up to set email alerts
|

Direct Binding of the Na–H Exchanger NHE1 to ERM Proteins Regulates the Cortical Cytoskeleton and Cell Shape Independently of H+ Translocation

Abstract: The association of actin filaments with the plasma membrane maintains cell shape and adhesion. Here, we show that the plasma membrane ion exchanger NHE1 acts as an anchor for actin filaments to control the integrity of the cortical cytoskeleton. This occurs through a previously unrecognized structural link between NHE1 and the actin binding proteins ezrin, radixin, and moesin (ERM). NHE1 and ERM proteins associate directly and colocalize in lamellipodia. Fibroblasts expressing NHE1 with mutations that disrupt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
452
3
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 389 publications
(488 citation statements)
references
References 57 publications
23
452
3
6
Order By: Relevance
“…In contrast, in migrating fibroblasts, NHE1 concentrates at the leading edge of the cell along the border of lamellipodia [41,40]. NHE1 abundance at the plasma membrane was recently shown to be regulated by direct ubiquitylation of the exchanger [154].…”
Section: Slc9a1-nhe1mentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, in migrating fibroblasts, NHE1 concentrates at the leading edge of the cell along the border of lamellipodia [41,40]. NHE1 abundance at the plasma membrane was recently shown to be regulated by direct ubiquitylation of the exchanger [154].…”
Section: Slc9a1-nhe1mentioning
confidence: 99%
“…NHE1 also participates in cell migration [82,40,41,150,79]. Inhibition or genetic ablation of NHE1 from fibroblasts significantly reduces migration speed and inhibits chemotaxis.…”
Section: Slc9a1-nhe1mentioning
confidence: 99%
See 1 more Smart Citation
“…Ezrin, for example, can associate with various membrane proteins such as CD44 (Tsukita et al, 1994), intercellular adhesion molecule-1,2 (Helander et al, 1996), Na-H exchanger (Denker et al, 2000), and type II c-AMP-dependent protein kinases (Dransfield et al, 1997). These interactions are established via its N terminus, whereas its C-terminal domain binds to F-actin in vitro (Turunen et al, 1994) and in vivo (Algrain et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…and osmotic cell shrinkage [31] . NHE1 deficiency leads to growth retardation, ataxia, and seizures [2] as well as abnormal cell morphology and adhesion [32] . It is reported that the asymmetrical expression and activation of NHE1 in cells generates a local intracellular pH gradient and thus induces or at least supports the rearrangement of the cytoskeleton by affecting cofilin, an actin-binding protein that increases the recycling of actin monomers [1] .…”
Section: Vacuolar Type H + -Atpases (V-atpases) Vacuolarmentioning
confidence: 99%